Tracking Progress Toward Sustainable Energy for All in South Asia - Portale, Elisa (World Bank, Washington, DC, 2014)
In declaring 2012 the International Year of Sustainable Energy for All, the UN General Assembly established three global objectives to be accomplished by 2030: to ensure universal access to modern energy services,1 to double the 2010 share of renewable energy in the global energy mix, and to double the global rate of improvement in energy efficiency relative to the period 1990 2010 (SE4ALL 2012). To sustain momentum for the achievement of the SE4ALL objectives, a means of charting global progress to 2030 is needed. The World Bank and the International Energy Agency led a consor¬tium of 15 international agencies to establish the SE4ALL Global Tracking Framework (GTF), which provides a system for regular global reporting, based on rigorous, yet practical, given available databases, technical measures. This note is based on that frame¬work (World Bank 2014). SE4ALL will publish an updated version of the GTF in 2015.